STEM education – the driving force towards human capital development - UMP, PNC (2019)
Universiti Malaysia Pahang (UMP) worked together with the Education Ministry’s Education Policy Planning and Research Division (BPPDP) and Pahang State Education Department to organise a colloquium on science, technology, engineering and mathematics (STEM) education.